Description Of Elderly Anxiety In The Face Of Death - Novita Maulidya Jalal (International Journal of Education, Vocational and Social Science, 2023)
The process of aging (aging) is a natural process faced by humans. In this process, the most crucial stage is the elderly stage. In this stage, in humans there is a natural decrease or change in physical, psychological and social conditions that interact with each other. The purpose of this research is to find out how the anxiety of the elderly in facing death is described. This study used qualitative research methods. The data collection method was carried out through an interview process with 1 (one) elderly subject aged 66 years. The interview was conducted using 7 open-ended questions related to the subject's readiness to face death. The results of this study indicate that the subject feels anxious and afraid of death, even though according to the subject death is a natural thing for every human being. This research is expected to provide insight regarding anxiety about death in the elderly from the point of view of psychological theory and research.